TEACHER PROFESSIONAL DEVELOPMENT IN THE ERA OF SOCIETY 5.0: REDEFINING COMPETENCIES FOR FUTURE CLASSROOMS - Sahri Romadon; Rufiatun Rufiatun; Alfi Anita Rahman; Falis Ulil Hidayah (Adisam Publisher, 2025)
This study aims to reanalyze teacher competency needs in the Society 5.0 era, where digital technology and artificial intelligence are deeply integrated into social, economic, and educational life. The role of teachers in this context is no longer limited to imparting knowledge but also encompasses the ability to manage collaborative, data-driven learning, and be responsive to technological developments and student needs. The study was conducted using a literature review method, examining various research findings, academic articles, and policy reports related to teacher professional development in the digital era. The results indicate that teacher professional development must be directed at strengthening digital literacy, critical thinking skills, pedagogical creativity, cross-cultural communication competencies, and ethical skills in the use of technology. Furthermore, the paradigm shift toward the classroom of the future demands a sustainable development framework that is adaptive to technological and social changes. Thus, this study emphasizes the importance of redefining teacher competencies to address the challenges and capitalize on the opportunities presented by Society 5.0 in education.